2011
DOI: 10.1094/pdis-11-10-0794
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics Between Fusarium pseudograminearum and Bipolaris sorokiniana in Wheat Stems Using Real-Time qPCR

Abstract: Moya-Elizondo, E. A., Jacobsen, B. J., Hogg, A. C, and Dyer, A. T. 2011. Population dynamics between Fusarium pseudograminearmn and Bipolaris sorokiniana in wheat stems using real-time qPCR. Plant Dis. 95:1089-1098.Fu.sarium pseudogratninearum and Bipolaris sorokiniana are causal agents of Fusadum crown rot and common root rot, respectively, of wheat and cause significant losses worldwide. Understanding the population dynatTiics between these two pathogens at late stages of wheat development is needed. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
(23 reference statements)
2
14
0
Order By: Relevance
“…Quantitative PCR is increasingly being used as a tool to investigate plant diseases, including those caused by soilborne Fusarium species (Nicholson et al 1998;Waalwijk et al 2004;Strausbaugh et al 2005;Hogg et al 2007;Evans et al 2010;Moya-Elizondo et al 2011;Knight et al 2012). The ability of qPCR to accurately measure levels of fungal biomass has important implications for evaluating traditional disease rating methods, detecting disease tolerance and assessing disease progress over the life of a plant.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR is increasingly being used as a tool to investigate plant diseases, including those caused by soilborne Fusarium species (Nicholson et al 1998;Waalwijk et al 2004;Strausbaugh et al 2005;Hogg et al 2007;Evans et al 2010;Moya-Elizondo et al 2011;Knight et al 2012). The ability of qPCR to accurately measure levels of fungal biomass has important implications for evaluating traditional disease rating methods, detecting disease tolerance and assessing disease progress over the life of a plant.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis suggests that these interactions are probably much more prevalent than previously appreciated (Stephens et al 2013). Reported pathogen-on-pathogen antagonisms encompass a diverse cross section of plant disease systems, including tree pathogens and wood rotting fungi (Boddy 2000;Gibbs and Smith 1978), storage rotting fungi (El Hadrami et al 2007;Yang et al 2008), foliar pathogens (Le May et al 2009;Nolan et al 1999), and root rots (Ledingham 1942;Moya-Elizondo et al 2011a;Scardaci and Webster 1981). Studies of foliar pathogens appear most common, with antagonisms reported among foliar pathogens of wheat, barley, and pea (da Luz and Bergstrom 1987;Le May et al 2009;Nolan et al 1999;Round and Wheeler 1978).…”
mentioning
confidence: 99%
“…In addition, some Fusarium wilts can develop with fewer CFUs than the detection threshold of the media (Nishimura 2007). Unlike conventional culturing approaches, real-time PCR assays have been demonstrated to accurately detect and quantify important plant pathogens (Jim enez-Fern andez et al 2011; Kuan et al 2011;Moya-Elizondo et al 2011;Bilodeau et al 2012). Moreover, an appropriate soil sampling protocol needs to be developed to accurately determine FOL DNA concentrations in soil by the real-time PCR assay.…”
Section: Discussionmentioning
confidence: 99%